Role of pelvic and para-aortic lymphadenectomy in epithelial ovarian cancers - Gupta, Pankush; Kumar, Sunesh; Singhal, Seema; Meena, Jyoti; Mathur, Sandeep; Kumar, Lalit (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Lymphadenectomy in epithelial ovarian cancers has remained a controversial subject. Lack of robust evidence on survival benefits and surgical morbidity associated questions its role in the era of adjuvant chemotherapy. The present study assessed pelvic and para-aortic lymph node removal in epithelial ovarian cancer in Indian women and tried to find clinicopathological correlation of nodal involvement and postoperative implications of lymphadenectomy. Methods: Thirty patients with diagnosis of epithelial ovarian cancer posted for primary debulking surgery were recruited and underwent staging laparotomy along with pelvic and para-aortic lymphadenectomy. Nodal involvement was confirmed on histopathology and various parameters which could predict nodal metastasis were assessed. Patients were followed up for 12 months post-surgery. Results: Nodal yield was ten for pelvic and four for paraaortic nodes. Pelvic node involvement was seen in 26.6% (8/30) of the patients and para-aortic in 15% (3/20) of the patients. Serous histology, higher grade, stage 3 and above, positive peritoneal cytology, omental involvement showed a higher lymph node involvement though not statistically significant. Para-aortic lymphadenectomy was associated with increased operating time, blood loss and longer hospital stay. Conclusions: Lymphadenectomy increases morbidity and decision should be based on predictors of nodal involvement.